ANALISIS PENERAPAN SISTEM E-FILLING DALAM UPAYA MENINGKATKAN KEPATUHAN WAJIB PAJAK BADAN DALAM PENYAMPAIAN SPT TAHUNAN - Wuriasih, Anik (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
This study aims to determine the implementation of e-filling in an effort to improve corporate taxpayer compliance in submitting Annual Notification Letters (SPT) at the Manokwari Pratama Tax Service Office and to find out the obstacles faced by corporate taxpayers in submitting Annual SPT at Manokwari KPP. This study uses qualitative analysis. The population and sample in this study were used as informants, while the number of informants was 12 executive staff of the Manokwari Primary Service Office. Methods of collecting data using interviews, and collecting documents. The data analysis technique used is the ratio calculation. The results of this study indicate that e-filing is quite capable of increasing corporate taxpayer compliance in submitting Annual Notification Letters (SPT) at the Manokwari Pratama Tax Service Office, and there are several obstacles that cause taxpayers to choose to submit manually, including server disturbances, lack of understanding of taxpayers, and lack of awareness of corporate taxpayers.